Photoreactive Coating Material as an Effective and Durable Antimicrobial Composite in Reducing Bacterial Load on Surfaces in Livestock - Ádám Kerek; Mátyás Sasvári; Ákos Jerzsele; Zoltán Somogyi; László Janovák; Zsolt Abonyi-Tóth; Imre Dékány (Biomedicines, 2022)
Titanium dioxide (TiO2) is a well-known photocatalytic compound that can be used to effectively reduce the presence of pathogens in human and animal hospitals via ROS release. The aim of this study was to investigate the efficacy of a polymer-based composite layer containing TiO2 and zinc oxide (ZnO) against Escherichia coli (E. coli) of animal origin. We showed that the photocatalyst coating caused a significant (p < 0.001) reduction in pathogen numbers compared to the control with an average reduction of 94% over 30 min. We used six light sources of different wattages (4 W, 7 W, 9 W, 12 W, 18 W, 36 W) at six distances (35 cm, 100 cm, 150 cm, 200 cm, 250 cm, 300 cm). Samples (n = 2160) were taken in the 36 settings and showed no significant difference in efficacy between light intensity and distance. We also investigated the influence of organic contaminant that resulted in lower activity as well as the effect of a water jet and a high-pressure device on the antibacterial activity. We found that the latter completely removed the coating from the surface, which significantly (p < 0.0001) reduced its antibacterial potential. As a conclusion, light intensity and distance does not reduce the efficacy of the polymer, but the presence of organic contaminants does.